THEORETICAL AND METHODOLOGICAL FOUNDATIONS FOR THE USE OF INNOVATIVE TECHNOLOGIES IN THE CONTEXT OF TEACHING ECONOMICS (World Bulletin of Management and Law, 2022)
Socio-economic changes in society require advanced professional education, in which the emphasis is shifted from a narrow-profile approach to training specialists to the multilateral intellectual and spiritual development of the student's personality. Such education can be provided only with the transition to student-centered learning based on innovative technologies. This article discusses about the theoretical foundations of innovative technologies in the pedagogical process, to develop methodological recommendations for teaching the discipline "Economics", based on pedagogical innovative technologies, the solution of which should be practical results.